2018
DOI: 10.1111/1467-9566.12717
|View full text |Cite
|
Sign up to set email alerts
|

What's in a name: are cultured red blood cells ‘natural’?

Abstract: The case of cultured red blood cells (RBCs) currently being grown in a laboratory for future use in human transfusion raises questions about the ontological status of such products of modern biotechnology. This paper presents results from a six-year ethnographic study involving interviews, focus groups and other forms of engagement with the scientific research team and other stakeholders, including public groups, which sought to understand respondents' reactions to cultured RBCs. These cells, derived from stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Studies involving the public generally reported support for cell and gene therapy research [16][17][18]24,29,30,34,38,42,45,46 with most participants in some studies confirming that they would be happy to donate their tissue for research 14,17,22,38 . A study showed that in the West, support for stem-cell research might vary by region with the highest level found among Canadians, then Americans and finally Europeans 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving the public generally reported support for cell and gene therapy research [16][17][18]24,29,30,34,38,42,45,46 with most participants in some studies confirming that they would be happy to donate their tissue for research 14,17,22,38 . A study showed that in the West, support for stem-cell research might vary by region with the highest level found among Canadians, then Americans and finally Europeans 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four of these papers related specifically to cell therapy while 11 pertained to gene therapy. Five of the included studies were conducted in the UK [12][13][14][15][16] , eight in the USA [17][18][19][20][21][22][23][24] , six in Canada [25][26][27][28][29][30] , two were conducted in Australia 31,32 and one each from Belgium 33 , China 34 , Germany 35 , Hungary 36 , Ireland 37 , Japan 38 , Korea 39 , South Korea 40 and Sweden 41 . One study included multiple countries across Europe 42 , three studies were set in Canada and USA [43][44][45] and one included Europe, USA and Canada 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Emma King studied the UK cultured blood project from 2009 to 2013 conducting laboratory observation, documentary analysis, and outreach work alongside the cultured blood team ( King, 2015 ). Emma and Catherine Lyall then conducted a study of public reactions to cultured blood, using focus groups and interviews ( Lyall and King, 2016 ; King, 2017 ; King and Lyall, 2018 ). This focus group and interview research was led from Anonymous University and funded by the same Scottish Funding Council grant funding the scientific research.…”
Section: Methodsmentioning
confidence: 99%
“…The project reported here by Emma and Catherine (Lyall and King, 2016;King and Lyall, 2018) was the first project to look specifically at public attitudes to cultured blood, although work is now being done by a team based at the University of Bristol.…”
Section: Markets and Anticipated Futuresmentioning
confidence: 99%
See 1 more Smart Citation